1995
DOI: 10.1111/j.1440-1827.1995.tb03441.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of macrophage‐derived foam cells and macrophage colony‐stimulating factor in pulmonary atherogenesis of cholesterol‐fed rabbits

Abstract: In order to investigate the role of monocyte/macrophages and their relationship to the expression of macrophage colony-stimulating factor (MCSF) in pulmonary atherosclerosis, lungs were excised from rabbits that had been fed for 60 and 90 days on a diet containing 0.5% cholesterol. In the lungs, fatty streaks and elevated foam cell lesions predominated in the large or medium-sized elastic pulmonary arteries, while massive accumulation of foam cells in the intima of muscular arteries produced marked luminal nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Up-regulation of M-CSF expression by LDL operates through activation of the nuclear transcription factor NF-kB [28], a factor which induces the expression of a number of molecules involved in the inflammatory response, such as leucocyte adhesion molecules, which are also rapidly upregulated in ExHC rats fed an HCD [22]. Local production of M-CSF has been described in vascular atherosclerotic lesions [9][10][11], and M-CSF may contribute to foam cell formation by upregulating monocyte expression of the LDL receptor and lipid metabolism [29][30][31]. In addition, genetic studies in mice have demonstrated a key role for M-CSF and its effects upon macrophage development and function in the pathogenesis of atherosclerosis [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up-regulation of M-CSF expression by LDL operates through activation of the nuclear transcription factor NF-kB [28], a factor which induces the expression of a number of molecules involved in the inflammatory response, such as leucocyte adhesion molecules, which are also rapidly upregulated in ExHC rats fed an HCD [22]. Local production of M-CSF has been described in vascular atherosclerotic lesions [9][10][11], and M-CSF may contribute to foam cell formation by upregulating monocyte expression of the LDL receptor and lipid metabolism [29][30][31]. In addition, genetic studies in mice have demonstrated a key role for M-CSF and its effects upon macrophage development and function in the pathogenesis of atherosclerosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although M-CSF has not been studied in lipid-induced renal injury, several studies point to a role for this molecule in monocyte recruitment in this form of renal injury. Local M-CSF expression and macrophage accumulation have been demonstrated in vascular atherosclerotic lesions [9][10][11]. Increased glomerular M-CSF expression has been implicated in glomerular macrophage accumulation and the development of glomerular injury in murine lupus nephritis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Circulating monocytes are precursors of the lipid-laden macrophages (foam cells) that contribute to inflammation in early and advanced atherosclerotic lesions (Ruan et al, 1995). However, it is not known which proteases are involved in CX3CL1 shedding from the VSMC surface.…”
mentioning
confidence: 99%
“…More recently, increased levels of cholesterol content in the lungs [20], systemic induction of 15-lipoxygenase activity [21], and massive accumulation of foam cells in the intima of lung muscular arteries during pulmonary atherogenesis [22] were reported.…”
mentioning
confidence: 99%